The diet quality of well adolescents: Do they really eat poorly? - Jacqueline Zimmerman; Alexis Santiago-Drakatos; Ronald Feinstein; Martin Fisher (Elsevier, 2023)
Background: A common assumption is that adolescents have poor eating habits. However, there is minimal data regarding adolescents' intake of macronutrients (i.e. protein, carbohydrate, and fats) and micronutrients (i.e. vitamins and minerals). In addition, few studies have used the Healthy Eating Index-2010 (HEI-2010) to assess diet quality of well adolescents. Objective: To determine diet quality among patients presenting for well care by using NDSR (Nutrition Data Systems for Research) nutrition analysis software and by calculating HEI-2010 scores. Methods: A convenience sample of adolescents presenting to clinic for well care was recruited. Participants completed a 24 hour dietary recall using the multiple pass method, a validated interviewing technique. Results for each participant were entered into NDSR version 2014, which provides a detailed nutrition analysis, and these results were also used to calculate a HEI-2010 score, which measures how well dietary intake conforms to the Dietary Guidelines for Americans in terms of amounts consumed from each food group. Results: Data from 48 adolescents (30 female, 18 male; mean age 16.5, range 12-20 years; 18 Hispanic, 11 Black, 5 White, 14 other) were analyzed. Body-mass-index (BMI) ranged from 16.0 to 38.1. Average total calories were 2054 (but there was a wide range of 683 to 4801 calories). Average calories for females and males were 1723 and 2604, respectively. Average percentages of calories from macronutrients were 33.2% from fat, 50.5% from carbohydrate, and 16.3% from protein. Micronutrient content was very low (< 53% of recommended Daily Values) for vitamins E and D; moderately low (61-76%) for zinc, magnesium, potassium and copper; minimally low (86-97%) for calcium, iron and vitamin B12; and normal (≥100%) for thiamin, riboflavin, niacin, folic acid, phosphorus, manganese, selenium and vitamins C, K, and B6. HEI scores were <50 ("poor") for 20 subjects and 51-79 ("needs improvement") for 13 subjects. Calorie consumption was insufficient to calculate an HEI score for 15 subjects and no subjects had an HEI score >80 ("good"). Conclusion: On some measures (distribution of macronutrients, intake of most vitamins and minerals), the adolescents in this study had sufficient diets by NDSR calculations. However, no subject had an HEI score indicative of good diet quality. It is possible that adolescents are consuming adequate macro- and micronutrients in the setting of processed, fortified foods, but that optimal consumption from each food group is lacking, resulting in lower diet quality scores on the HEI.